Evaluation of current physical symptoms and psychological sufferings of patients during attending department of palliative medicine in a tertiary care hospital - Urmy, Sabikun Naher; Alam, Afroja; Sharmin, Shah Noor; Aktar, Mossa Nupur; Noor, Rahat; Sultana, Rakiba; Shaidur Rahman, M.; Haque, Kazi Sanzida (International Journal of Research in Medical Sciences, 2024)
Background: Empirical evidence indicates that anxiety and depression in cancer patients are often overlooked, leading to insufficient assistance for their psychosocial needs. Distinguishing between clinical anxiety and depression and the typical emotional distress post-cancer diagnosis can be challenging but holds significant implications for coping strategies and outcomes. The aim of this study was to assess current physical symptoms and psychological sufferings of patients’ during attending in a Palliative care department of a tertiary care hospital. Methods: This cross‐sectional study was conducted among 191 patients with cancer attending the department of palliative medicine, Bangabandhu Sheikh Mujib Medical University, Dhaka, Bangladesh from November 2021 and March 2022. Data was collected by face‐to‐face interview using a structured questionnaire. Depression and anxiety were evaluated using a modified version of the primary care evaluation of mental disorders guide. Results: 47 participants (20.7% prevalence of depressive disorders and 13.9% prevalence of anxiety disorders) met the diagnostic criteria for at least one anxiety or depressive disorder, according to the Diagnostic and Statistical Manual of Mental Disorders, Fourth Edition. The 95% confidence interval for these results was between 20.2 and 29.0. Conclusions: In summary, depression and anxiety disorders are prevalent among patients in palliative care, significantly reducing the quality of life for those facing cancer-related mortality.